2005
DOI: 10.1016/j.cogdev.2005.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Children's understanding of ambiguous figures: Which cognitive developments are necessary to experience reversal?

Abstract: Running head: Children's understanding of ambiguous figures Acknowledgements We would like to thank the staff and pupils of Beaconhurst, Borestone, Braehead, Cambusbarron schools, and the University of Stirling Psychology Playgroup for their kind cooperation, and Robin N. Campbell and Anton Kühberger for comments on an earlier draft of this manuscript.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
66
1
12

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(82 citation statements)
references
References 17 publications
3
66
1
12
Order By: Relevance
“…When looking at these-objectively stable-pictures, people continuously alternate between two mutually exclusive interpretations (e.g., from a face to a vase and vice versa; Kleinschmidt, Büchel, Zeki, & Frackowiak, 1998;Long & Toppino, 2004). These stimuli have been used to explore numerous perceptual phenomena, including binocular rivalry (Blake & Logothetis, 2002;Meng & Tong, 2004), the influence of cues on perception (Panichello, Cheung, & Bar, 2013, for an overview), the ability of children to switch between the two interpretations (Doherty & Wimmer, 2005;Gopnik & Rosati, 2001; M.C. Wimmer & Doherty, 2011), the brain areas associated with perceptual switches (Britz, Landis, & Michel, 2009;Kleinschmidt et al 1998;Lumer, Friston, & Rees, 1998;Zaretskaya, Thielscher, Logothetis, & Bartels, 2010), and perceptual hysteresis (Hock et al, 1993).…”
mentioning
confidence: 99%
“…When looking at these-objectively stable-pictures, people continuously alternate between two mutually exclusive interpretations (e.g., from a face to a vase and vice versa; Kleinschmidt, Büchel, Zeki, & Frackowiak, 1998;Long & Toppino, 2004). These stimuli have been used to explore numerous perceptual phenomena, including binocular rivalry (Blake & Logothetis, 2002;Meng & Tong, 2004), the influence of cues on perception (Panichello, Cheung, & Bar, 2013, for an overview), the ability of children to switch between the two interpretations (Doherty & Wimmer, 2005;Gopnik & Rosati, 2001; M.C. Wimmer & Doherty, 2011), the brain areas associated with perceptual switches (Britz, Landis, & Michel, 2009;Kleinschmidt et al 1998;Lumer, Friston, & Rees, 1998;Zaretskaya, Thielscher, Logothetis, & Bartels, 2010), and perceptual hysteresis (Hock et al, 1993).…”
mentioning
confidence: 99%
“…In addition, there are significant performance differences as well, within the age range from 3 to 5 years. Doherty and Wimmer (2005) found that 3-year-old children cannot even report both interpretations of such ambiguous images as the duck-rabbit or the man-mouse figures. However, 4-year-old children can easily interpret the ambiguous figures in both ways.…”
Section: Other Forms Of Bi-stable Perceptionmentioning
confidence: 99%
“…Criticizing this assumption of automatic and spontaneous reversal, the main alternative approach puts the emphasis on knowledge of ambiguity and reversibility of a given pattern (Doherty & Wimmer, 2005). For example, Rock, Gopnik, and Hall (1994) and Rock and Mitchener (1992) have shown that many subjects fail to report spontaneous reversal if they were not informed of the possible interpretations before viewing the ambiguous pictures.…”
Section: Theoretical Explanationsmentioning
confidence: 99%